Grammatical Differences and Its Impact on Juristic Issues - Dr Abd-ul-Qayyum Al-Madni (Hazara Islamicus, 2012)
This research paper deals with the differences of the Arabic grammarians and linguists and its impact on Islamic jurists and jurisprudence. Arabic is the language of the Qur'an and Islam, and both can be correctly understood by knowing Arabic and its grammar. The linguists and jurists differed with each other in juristic issues and cases. This difference of opinion was based on the differences among the linguists and grammarians in grammatical rules and principles.